Biodihydroxylation of substituted quinolines and isoquinolines by recombinant whole-cell mediated biotransformations. Issue 46 (17th November 2016) - Zia, Muhammad Farooq; Vasko, Ágnes G.; Riedl, Zsuzsanna; Hametner, Christian; Hajós, György; Mereiter, Kurt; Mihovilovic, Marko D.
Abstract: The recombinant whole-cell mediated biooxygenation of various quinolines and isoquinolines was investigated employing three different dioxygenases of bacterial origin. Substrate screening focused on the biotransformation of cyano-substituted azaarenes, in particular. Efficiently accepted substrates were submitted to scale-up of the enzyme mediated reaction to preparative scale. The regio- and stereoselectivity of the obtained metabolites was established by NMR and X-ray diffraction after appropriate derivatization. Graphical abstract: